Investment Attractiveness Assessment (Comparison Batu City and Malang City) (International Conference of Graduate School on Sustainability (ICGSS), 2020)
This study aims to: 1) compare  factors of investment attractiveness  between Batu City and Malang City, and 2) compare rating of investment attractiveness between  Batu City and Malang City. Data analyzed uses Independent Sample t Test, with 80 investors as a respondent, 40 investors from Batu City and 40 investors from Malang City. Based the results of  independent samples test obtained: 1) there are significant differences in the factors of investment attractiveness between Batu City and Malang City. The distinguishing factors are: business licensing system, leadership, politics and security. Batu City has a higher average value than Malang City in that factors; 2) there is a significant difference in the investment attractiveness rating between Malang City and Batu City. The rating of investment attractiveness of Batu City is more higher than Malang City